Emotional development and autism spectrum disorders - Reyna, Cecilia (2011)
This paper reviews basic concepts of emotional process and its development during childhood, focusing on the particularities that occur in children with autism spectrum disorders. The interrelation between theory of intersubjectivity and theory of mind is emphasized; it allows obtaining a more accurate picture of this disorder.